2019
DOI: 10.5194/acp-19-15377-2019
|View full text |Cite
|
Sign up to set email alerts
|

Gravity waves in the winter stratosphere over the Southern Ocean: high-resolution satellite observations and 3-D spectral analysis

Abstract: Abstract. Atmospheric gravity waves play a key role in the transfer of energy and momentum between layers of the Earth's atmosphere. However, nearly all general circulation models (GCMs) seriously under-represent the momentum fluxes of gravity waves at latitudes near 60∘ S, which can lead to significant biases. A prominent example of this is the “cold pole problem”, where modelled winter stratospheres are unrealistically cold. There is thus a need for large-scale measurements of gravity wave fluxes near 60∘ S,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
102
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(111 citation statements)
references
References 94 publications
8
102
1
Order By: Relevance
“…Retrieval noise and vertical resolution are balanced to give an effective vertical resolution varying between 7 km at 20 km altitude and 15 km at 60 km altitude (Ern et al, 2017;Hoffmann & Alexander, 2009;Sato et al, 2016). Noise is lowest between 20 and 60 km, at approximately 1.4 to 2 K (Ern et al, 2017;Hindley et al, 2019;Hoffmann & Alexander, 2009). Sensitivity of the retrieval to GWs is discussed in Meyer and Hoffmann (2014), Hindley et al (2019), and Ern et al (2017).…”
Section: Three-dimensional Airs/aqua Satellite Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieval noise and vertical resolution are balanced to give an effective vertical resolution varying between 7 km at 20 km altitude and 15 km at 60 km altitude (Ern et al, 2017;Hoffmann & Alexander, 2009;Sato et al, 2016). Noise is lowest between 20 and 60 km, at approximately 1.4 to 2 K (Ern et al, 2017;Hindley et al, 2019;Hoffmann & Alexander, 2009). Sensitivity of the retrieval to GWs is discussed in Meyer and Hoffmann (2014), Hindley et al (2019), and Ern et al (2017).…”
Section: Three-dimensional Airs/aqua Satellite Observationsmentioning
confidence: 99%
“…In the vertical, we interpolate onto a regular 1.5 km altitude grid. Measurements above 60 km and below 20 km are set to zero, with a smooth half-bell taper applied to reduce edge effects near the boundaries as described by Hindley et al (2019). This limits our visibility to vertical wavelengths greater than around 40 km.…”
Section: Three-dimensional Airs/aqua Satellite Observationsmentioning
confidence: 99%
“…In austral winter, the westerlies of the polar night jet (PNJ) allow these mountain waves to propagate deeply into the middle atmosphere where they deposit their momentum and decelerate the mean stratospheric flow [2][3][4] . So far, mainly satellite-based instruments are utilized for estimations of the stratospheric gravity wave momentum that is transported vertically [5][6][7][8][9][10][11][12][13][14][15][16] . Due to the observational filter of these instruments, only a part of the full wave spectrum is included.…”
mentioning
confidence: 99%
“…AIRS is not the focus of this study, but for information I find that in practice the vast majority of vertical wavelengths measured in AIRS are generally between 15 and 25km (e.g. Hindley et al, 2019). Shorter vertical wavelengths tend to be lost below the noise threshold, and longer vertical wavelengths tend to be underestimated due to only a few cycles being present in the vertical, which reduces the signal to noise.…”
mentioning
confidence: 99%
“…Shorter vertical wavelengths tend to be lost below the noise threshold, and longer vertical wavelengths tend to be underestimated due to only a few cycles being present in the vertical, which reduces the signal to noise. We did not apply a correction in the measured vertical wavelength in Hindley et al (2019) because I found that the measurement error in the vertical wavelength of around 10-25% was comparable to the correction factor, so I didn't want to C4 incorrectly apply it and introduce a further source of error. Here, error in the vertical wavelength measurement of the S3D method could be similar, so they may have the same problem, but the authors do not discuss or quantify that here.…”
mentioning
confidence: 99%